2008
DOI: 10.1088/1126-6708/2008/05/043
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the ΔS= 1 weak Hamiltonian in the SU(4) chiral limit through topological zero-mode wave functions

Abstract: A new method to determine the low-energy couplings of the ∆S = 1 weak Hamiltonian is presented. It relies on a matching of the topological poles in 1/m 2 of three-point correlators of two pseudoscalar densities and a four-fermion operator, measured in lattice QCD, to the same observables computed in the ǫ-regime of chiral perturbation theory. We test this method in a theory with a light charm quark, i.e. with an SU(4) flavour symmetry. Quenched numerical measurements are performed in a 2 fm box, and chiral per… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…The aim is to understand the role of the charm quark in the ∆I = 1/2 enhancement. Our work extends the results for the GIM limit m c = m u in [30,31]. The numerical techniques developed in [32] have been instrumental in the lattice QCD computation of amplitudes involving eye diagrams.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The aim is to understand the role of the charm quark in the ∆I = 1/2 enhancement. Our work extends the results for the GIM limit m c = m u in [30,31]. The numerical techniques developed in [32] have been instrumental in the lattice QCD computation of amplitudes involving eye diagrams.…”
Section: Discussionsupporting
confidence: 73%
“…Results in the GIM limit were obtained in [30,31] from quenched QCD simulations with overlap quarks. It was found that in this case the I = 2 amplitude is already very close to its physical value, and that a significant enhancement is already present.…”
Section: Introductionmentioning
confidence: 99%
“…In this section the propagator techniques are applied to an ongoing project to study the role of the charm quark in the explanation of the ∆I = 1/2 rule [18,19,20]. Our physics results are presented in a companion paper [21]; preliminary results from this study have also been reported in Ref.…”
Section: Eye Diagrams For K → πmentioning
confidence: 99%
“…Our main target application for this setup lies within a long-term project to study the role of the charm quark in the ∆I = 1/2 rule for non-leptonic kaon decay [18,19,20]. More specifically, we will consider the severe signal-to-noise ratio arising in the computation of "eye diagrams" (penguin contractions), that appear as contributions to K → π transition amplitudes mediated by the ∆S = 1 weak effective Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts to study the ∆I = 1/2 rule on the lattice have been made. For example, an ongoing project based on the role of the charm quark has been developed in [43,44,45,46], see also [47].…”
Section: The ∆I = 1/2 Rulementioning
confidence: 99%